Analisis Rasa Percaya Diri Anak Usia 5-6 Tahun Melalui Metode Bernyanyi di TK Methodist Mandala - Yohana Simangunsong; Anada Leo Virganta; Gita Noveri Eza; May Sari Lubis; Suri Handayani Damanik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study is to analyze the self-confidence of 5-6-year-old children through the singing method at TK Methodist Mandala. The subjects of this study are 22 children, consisting of 13 boys and 9 girls. The instruments used in this research include observation, interviews, and documentation. The results indicate that the singing method significantly enhances children's self-confidence. Most of the children showed positive developments in their courage to perform in front of the class, willingness to express their opinions, and enthusiasm to participate in activities. However, there are four children who still exhibit a lack of self-confidence, influenced by internal factors such as fear and inferiority, as well as external factors like the lack of parental involvement and economic conditions.